PENERAPAN MESIN TUSUK SATE UNTUK MENINGKATKAN UMKM TUSUK SATE DI DESA KRASAK - Sukroni; Gunawan, Leo Van; Ghozali, Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The aim of this activity is to increase skewer production at skewer MSMEs in Krasak village. The transition from the process of making skewers manually to using a skewer machine. Provide education on the use of skewer machines. Testing the performance of the satay skewer machine found 286 skewers in 1 minute compared to the manual process which produced 25 skewers in 1 minute. From these results it can be concluded that the use of skewer machines is very effective and can increase skewer production in skewer SMEs in Krasak village.